Low-cost PWM speed controller for an electric mini-baja type vehicle - De Lucena, Samuel Euzédice [UNESP] (2007)
This paperwork presents a Pulse Width Modulation (PWM) speed controller for an electric mini-baja-type car. A battery-fed 1-kW three-phase induction motor provides the electric vehicle traction. The open-loop speed control is implemented with an equal voltage/frequency ratio, in order to maintain a constant amount of torque on all velocities. The PWM is implemented by a low-cost 8-bit microcontroller provided with optimized ROM charts for distinct speed value implementations, synchronized transition between different charts and reduced odd harmonics generation. This technique was implemented using a single passenger mini-baja vehicle, and the essays have shown that its application resulted on reduced current consumption, besides eliminating mechanical parts. Copyright © 2007 by ABCM.